The Bullying Experience in High School Students by the Teacher is reviewed from Psychological Theory - Barokatul Asiyah (International Consortium of Education and Culture Research Studies, 2020)
Bullying at school is the most vulnerable thing to happen. Bullying is not only done by peers, but it can also be done by teachers. If bullying is done by the teacher, it will threaten the welfare of the students. Students will feel insecure and bad things can happen, ranging from student anxiety, dropouts, and suicide. Based on the experience of a guest speaker by a bullyng teacher while in grade 2 of high school there are some feelings that arise as a result of the bullying. Participants had felt very down and wanted to get out of school. The participant claimed he was bullied because he was deemed incapable of doing the tasks of the teacher, besides that he also had a physical that was considered not as beautiful as other friends. The response of participants during getting bullies is anger, self-introspection, trying to be patient, but participants were finally able to continue their schooling to finish because there are two things that strengthen it, namely: social support and self acceptance. With that, the participant was finally able to finish his school well, even he passed the national examination with rank 2 in the district.